Tunable broadband absorber based on a layered resonant structure with a Dirac semimetal. Issue 12 (8th March 2023) - Li, Wenxin; Ma, Jing; Zhang, Huafeng; Cheng, Shubo; Yang, Wenxing; Yi, Zao; Yang, Hua; Zhang, Jianguo; Wu, Xianwen; Wu, Pinghui
Abstract : Here, the broadband absorber can achieve electromagnetic wave absorption at 18–28 THz and realize multi-layer Fermi energy tunable. In addition, it shows high irrelevance between incident angle and polarization direction. Abstract : With the development of science and technology, intermediate infrared technology has gained more and more attention in recent years. In the research described in this paper, a tunable broadband absorber based on a Dirac semimetal with a layered resonant structure was designed, which could achieve high absorption (more than 0.9) of about 8.7 THz in the frequency range of 18–28 THz. It was confirmed that the high absorption of the absorber comes from the strong resonance absorption between the layers, and the resonance of the localised surface plasmon. The absorber has a gold substrate, which is composed of three layers of Dirac semimetal and three layers of optical crystal plates. In addition, the resonance frequency of the absorber can be changed by adjusting the Fermi energy of the Dirac semimetal. The absorber also shows excellent characteristics such as tunability, absorption stability at different polarisation waves and incident angles, and has a high application value for use in radar countermeasures, biotechnology and other fields.